DISTRIBUTION OF TRACE ELEMENTS BETWEEN CARBONATE MINERALS AND AQUEOUS SOLUTIONS - PRECIPITATION RATES AND OVERGROWTH COMPOSITIONS - Rimstidt J.D.; Balog A.; Webb J. (My University, 1998)
The experimental distribution coefficients, K'd, for trace elements in carbonate minerals show a systematic pattern of behavior that differs from that expected if the distribution were controlled by equilibrium thermodynamics. Regression of experimental distribution coefficients, K'd, from the literature shows that they correlate well with the quotient of the solubility products of the trace element and host carbonate. However, the slope of the correlation line differs from that predicted by equilibrium theory in a way that suggests that the experiments are affected by a kinetic process, whereby the trace element is incorporated into the growing carbonate crystal at a rate that is either faster or slower than the incorporation of Ca. The correlations predict that the K'd for elements that form rhombdohedral carbonates (e.g., Cd, Zn, Cu, Mn, etc.) is expressed by K'd=1.6KMCO3KTrCO3 0.57 for calcite and K'd=4.1KMCO3KTrCO3 0.57 for siderite. These correlations can be used to estimate the K'd values for cases where no experimental data are available, including for other phases and other temperatures.Thus, the experimental K'd values can be used to understand general trends in trace element behavior. Analysis of K'd for calcite shows that this mineral can effectively sequester a variety of toxic cations (e.g., Pb, Cd, Cu, etc.) from solution, so precipitation of calcite from contaminated solutions may provide an effective method of environmental remediation. On the other hand, values of K'd should be used with caution when interpreting ancient geochemical environments for carbonates, because K'd values are strongly rate-dependent and the rates of mineral precipitation are seldom known.